Correlated leading baryon-antibaryon production in e(+)e(-) -> c(c)over-bar -> Lambda(+)(c)(Lambda)over-bar(c)(-)X - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2010)
We present a study of 649±35 e⊃+e⊃-→cc̄ events produced at √s±10.6GeV containing both a Λc+ baryon and a Λ̄c- antibaryon. The number observed is roughly 4 times that expected if the leading charmed hadron types are uncorrelated, confirming an observation by the CLEO Collaboration. We find a 2-jet topology in these events but very few additional baryons, demonstrating that the primary c and c̄ are predominantly contained in a correlated baryon-antibaryon system. In addition to the charmed baryons we observe on average 2.6±0.2 charged intermediate mesons, predominantly pions, carrying 65% of the remaining energy.© 2010 The American Physical Society.